Hubungan Antara Pemahaman Konsep Fisika Dasar dan Keterampilan Klinis Mahasiswa Keperawatan - Amalia Bintang Firshana; Aryanti Putri Lestari; Dinda Cinthya Nur Novalinda; Luluq Apriliana Fauziah; Winda Nafisha; Zahra Aninda Zalianti; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Understanding the basic concepts of physics plays an important role in supporting the clinical skills of nursing students, particularly in the application of scientific principles to nursing practices such as measuring patients’ blood pressure, administering intravenous infusions, and operating medical devices. This journal article examines the relationship between the level of understanding of basic physics concepts and the clinical skills of nursing students. Therefore, physics serves as a fundamental foundation in developing the professional competence of nurses.